2017
DOI: 10.1080/13685538.2017.1350156
|View full text |Cite
|
Sign up to set email alerts
|

Reference database of hematological parameters for growing and aging rats

Abstract: The present study determined the normal values for absolute and relative hematological parameters in Wistar rats from 2 to 24 months for male and female rats. The results can be used in studies of effects of aging, feeding, and medications on growing and aging rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
13
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 9 publications
8
13
0
4
Order By: Relevance
“…Despite the fluctuating food and water intake, the body weight measurements showed elevating trends, indicating normal development of the TS. Similar body weight trends were also reported by other authors [ 30 , 31 , 32 ]. Hence, it is concluded that the fluctuations observed in the food and water intake did not cause any treatment-related effects in the TS.…”
Section: Discussionsupporting
confidence: 91%
“…Despite the fluctuating food and water intake, the body weight measurements showed elevating trends, indicating normal development of the TS. Similar body weight trends were also reported by other authors [ 30 , 31 , 32 ]. Hence, it is concluded that the fluctuations observed in the food and water intake did not cause any treatment-related effects in the TS.…”
Section: Discussionsupporting
confidence: 91%
“…Our study has limitations. For example, we lack research of any influence of seasonal and age [ 70 ] changes on biochemical and haematological analytes in Sprague-Dawley rats. Besides, the number of parameters is limited.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the experiment, relevant hematological parameters were analyzed in order to evaluate the general health status of rats. None of the examined parameters exceeded the reference values [ 16 ]. However, the statistical analysis of the RBC parameters confirmed that AgNPs coating had an influence on HGB (ANOVA, p = 0.016), MCH (ANOVA, p = 0.003) and MCHC (ANOVA, p = 0.003), MCV (ANOVA, p = 0.004), and RDWc (ANOVA, p = 0.003) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%